A semi-empirical analytical model to predict the axial cutting force of AZ31B magnesium extrusions. (October 2018) - Magliaro, John; Shery, Peter; Smith, Ryan; Altenhof, William; Beeh, Elmar; Straßburger, Philipp; Grünheid, Thomas
Abstract: In several industries where weight reduction is a crucial design goal, especially transportation, magnesium alloys are becoming a favourable option to further innovate since magnesium is the lightest structural metal available. Cylindrical, seamless extrusions composed of AZ31B magnesium alloy were subjected to quasi-static and dynamic axial cutting to assess the potential for magnesium alloys to be exploited for crashworthiness applications. Geometrically similar aluminum extrusions composed of AA6061-T6 and AA6082-T6 alloys, which are commonly utilised for energy absorbers, were also tested under similar loading conditions to provide data for comparison. A semi-empirical model to predict the cutting forces in magnesium extrusions was derived using the experimental findings from this study. This revised model accounts for the discontinuous chip formation mechanism and frictional effects more appropriately than previously developed models. The extrusions possessed 1.5 mm wall thicknesses, outer diameters of 57 mm or 62 mm, and free lengths of 180 mm. Quasi-static tests were conducted on a Tinius-Olsen compression machine and dynamic tests on a drop tower with a 57 kg falling mass at an impact velocity of 7 m/s. Under the observed cutting deformation mode, all specimens produced evenly sized, petalled sidewalls. However, for the aluminum extrusions long, continuous chips formed ahead of the cutter while short, discontinuous chips formed for the magnesium extrusions. The corresponding energy dissipation ranged from 1.23 kJ to 3.57 kJ for the aluminum specimens and 0.63–0.72 kJ for the magnesium specimens. Highlights: Quasi-static and axial cutting of thin walled magnesium and aluminum extrusions. Multiple wall thicknesses, alloys, blade numbers and loading rates considered. Collected data used to develop a semi-empirical axial cutting model of magnesium. High speed photographic imaging permits close inspection of deformation modes.